From Policy to Practice: Teachers’ Perception of the Implementation of Merdeka Curriculum at Vocational High Schools in Lubuklinggau - Yulfi; Ayu Oktaviani; Episiasi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The aim of this research was to investigate English teachers’ perceptions about the implementation of the Merdeka Curriculum at vocational high schools in Lubuklinggau. This research used a descriptive qualitative method. English Teachers at several vocational high schools in Lubuklinggau who implemented the Merdeka Curriculum were included as subjects in the research. The schools were SMK Negeri 2 Lubuk Linggau, SMK Negeri 3 Lubuk Linggau, and SMK Negeri 4 Lubuk Linggau. In collecting data, questionnaires and interviews were used. Data from the questionnaire were analyzed using descriptive statistics. Interview data were reviewed descriptively to yield reliable, trustworthy findings. The result of this study was useful for evaluating the Education Office of Lubuklinggau and all elements that proposed the implementation of the Merdeka Curriculum. It showed that, among the English teachers’ perceptions toward the implementation of the Merdeka Curriculum, 4 English teachers were in the very good category, with a percentage of 66.66%. However, 2 English teachers were in the good category (33.33%). While there is no English teacher for the fair, bad, and very bad category (0%). It means that most of the English teachers at Vocational schools in Lubuklinggau who implemented the Merdeka Curriculum have a very good understanding and perception of its implementation at their schools. There are some important points related to English teachers’ perceptions, such as the fact that they are the main factor in determining the success of implementing the curriculum, so optimal socialization and training are very important for them. The government can also give greater attention to the provision of facilities and infrastructure for each school to support the learning process. Keywords: English Subject, Implementation, Merdeka Curriculum, Perception